Business environment effect on business visitor arrivals to New Zealand. Issue 17 (2nd September 2021) - Gani, Azmat; Clemes, Michael D.
ABSTRACT: This research investigates the impact that New Zealand's business environment has on its international business visitor arrivals. Within a gravity modelling framework, data for twenty-four main visitor origin countries are used for empirical analysis for the period 2004–2013. The core contribution of our research is that our empirical results provide strong evidence that the interaction of internet diffusion, commercial bank presence and shipping services with international trade are statistically significant variables. New Zealand's business infrastructure also correlates with foreign business visitors. We conclude that more open trade policies, combined with an improved business environment, provide the added benefits of attracting more international business visitors offering a subsequent, positive impact on the New Zealand tourism industry.